FRACTAL ANALYSIS FOR TWO DIMENSIONAL OF YEAST SYSTEM USING BOX COUNTING METHOD - KRISTIANI S (NIM: 10114076), MARIA
Yeast is a single-cell microorganism belongs to the fungi kingdom class. In this final project, fractal analysis is used by using the value of the fractal dimension of a yeast colony. The process of calculating fractal dimensions uses the methods of box counting and Monte Carlo. The Monte Carlo method was used to obtain the extent of the yeast cell colony and the box counting method was used to derive values from the yeast colonic fractal dimension of the cell. Based on the simulation it was found that the average value of fractal dimension of stationary yeast cell equals two, the fractal dimension value of yeast cell colony with the last child is smaller than yeast colony with the last adult child. Furthermore, when the fractal dimension of a yeast colony approached two, each yeast cell obtain higher quality of nutrients